Natural Experiments in Labor Economics and Beyond - Simon Jäger; Jörn-Steffen Pischke (Wirtschaftsdienst)
Abstract This year’s Nobel Prize in Economics honoured David Card of the University of California, Berkeley “for his empirical contributions to labour economics”, and Joshua Angrist of MIT and Guido Imbens of Stanford University “for their methodological contributions to the analysis of causal relationships”. We explain how the laureates revolutionised the analysis of causal relationships in empirical economics through the methodology of natural experiments. Three examples from the German labour market on the effects of minimum wages, code-termination and unemployment insurance illustrate how natural experiments yield new insights, which can form the foundation for evidence-based policy advice.